The Relationship Between Body Mass Index And Blood Sugar Levels In Patients With Diabetes Mellitus Type 2 In The Working Area Of Telaga Health Centre Gods Of Bengkulu City Year 2024 - Elpina, Elpina; Pebriani , Emi; Tranado, Hengki (CV. Utami, 2025)
The International Diabetes Federation in 2021 reported that 537 million adults (20-79 years old) were living with diabetes worldwide. This number is expected to increase to 643 million (1 in 9 adults) by 2030 and 784 million (1 in 8 adults) by 2045. The purpose of this study was to determine the relationship between body mass index and blood sugar levels during type 2 diabetes mellitus patients in the Telaga Dewa Health Centre Working Area, Bengkulu City in 2024.The research method used was descriptive quantitative research with a cross sectional approach. The sampling technique used was total sampling technique with the number of samples in this study 74 people representing all patients with type 2 diabetes mellitus in the Telaga Dewa Health Centre Working Area, Bengkulu City.The results of the univariate test analysis of most respondents (55.4%) with normal body mass index and most respondents (63.5%) with normal blood sugar levels. The results of bivariate analysis obtained the results of BMI (0.000) with free sexual behaviour in adolescents. There is a relationship between BMI and blood sugar levels during type 2 diabetes mellitus patients in the Telaga Dewa Health Centre Working Area, Bengkulu City in 2024.Researchers suggest that the Telaga Dewa Community Health Centre, Bengkulu City, can increase public knowledge in the form of counseling efforts regarding risk factors that can affect blood sugar levels.